Science Communication Desperately Needs More Aligned Recommendation Algorithms - Hoang, Lê Nguyên (Frontiers in Communication, 2020)
With 1-billion watch-time hours per day, YouTube now plays a major role in communication. Unfortunately, a large amount of misinformation is produced and widely shared on this platform (Donzelli et al. (2018); Allgaier (2019); Loeb et al. (2019)). In this paper, after providing a brief overview of the creation of science contents on YouTube, we particularly insist on the importance of YouTube’s automated recommendations. We then discuss the main challenges to make such recommendations aligned with quality science communication.